+Teacher’s Strategies in Teaching Speaking to Students Third Grade at SMAN 1 Taliwang - Neli Purnama; I Made Sujana; Kurniawan Apgrianto (Jurnal Ilmiah Profesi Pendidikan, 2022)
Speaking instruction is a major concern in many language programs, and instructional strategy cannot be used to influence learning outcomes. In terms of teaching speaking strategies, it is paradoxical that the majority of students in third grade were unable to speak English. This study aims to determine the strategies used by teachers at SMAN 1 Taliwang in teaching speaking skills. This thesis used a qualitative descriptive method. The subjects of this study were two English teachers at SMAN 1 Taliwang. Data were collected by observing and interviewing teachers. Then, the data analysis procedures in this study include data compaction, data presentation, and drawing conclusions. The results of this study there are three types of strategies used by teachers, namely cognitive strategies, metacognitive strategies, and social strategies. The cognitive strategies used by the teacher’s consist of memorizing and drilling. Which are included the metacognitive strategies that the teacher uses are questions, outdoor learning, pre-evaluation, and giving stimulus. Included in the social strategies used by teachers are peer-to-peer, presentations and assignments, dialogues, and discussions and presentations.